Carbon and nitrogen isoscape of particulate organic matter in the East China Sea. (September 2021) - Ho, Pei-Chi; Okuda, Noboru; Yeh, Chih-Fu; Wang, Pei-Ling; Gong, Gwo-Ching; Hsieh, Chih-hao
Highlights: Marine phytoplankton determine stable isotope signals of particulate organic matter (POM) in the East China Sea. δ 13 C value of euphotic POM increases with phytoplankton biomass. δ 15 N value of euphotic POM may be determined by nutrient deficiency and microbial activity in the East China Sea. Abstract: The isoscape of particulate organic matters (POM) in the euphotic zone at the shelf of the East China Sea (ECS) is affected by hydrological interactions and biological activities. Based on the stable carbon and nitrogen isotope values (δ 13 C and δ 15 N) and C:N ratio of POM (0.7 to 50 μm) in the euphotic zone of the ECS from 2008 to 2018 with a total of 113 samples, we inferred their sources and then investigated what hydrographical and biological conditions determined these spatio-temporal variations through synoptic and intensive seasonal monitoring. The isotopic signatures (δ 13 C: −26.9 to −12.4‰, δ 15 N: −1.0 to 10.8‰) and C:N ratios (4.4–9.0) of euphotic POM varied within the range of values reported for marine phytoplankton, suggesting limited contribution of terrigenous POM to the shelf of the ECS. The δ 13 C values of POM increased with the increase of chlorophyll- a (chl- a ) concentration at the depth of chl- a maximum and the δ 15 N values decreased near the Changjiang River plume and inner shelf with freshwater input and coastal upwelling in summer. This indicated that phytoplankton production was enhanced by high nutrient supply and warmer temperature. Besides, the δ 15 N values were higher under lower inorganic nitrogen nutrient concentrations, and were negatively correlated with POM C:N ratio (i.e., δ 15 N value was less negative with higher nitrogen content in POM). Such correlations may suggest the enhanced trophic interactions in microbial food chains in oligotrophic environments, where phagotrophic protists with high δ 15 N values could be included into the size fraction (0.7–50 μm) of POM. Based on our study, the spatial and temporal δ 13 C and δ 15 N isoscape of euphotic POM serves as an ecological indicator to infer primary production and plankton food web properties of the East China Sea.